Концепция баллистического лазерного гравиметра повышенной эффективности - Болюх, Владимир Федорович; Винниченко, Александр Иванович (НТУ "ХПИ", 2011)
Conception of ballistic laser to the gravimeters promoted efficiency with the modernized system of electro heater system elements, providing a minimum temperature gradient on the axis of gravimeters, is offered, and with an impulsive induction-dynamic drive providing direct transformation of electric energy to kinetic energy of the vertical moving of trial body with an optical reflector, diminished sizes of non-working area of vacuuming chamber, improved regulation descriptions, in default of mechanical contact cooperations.
Keywords: баллистический лазерный гравиметр; свободное падение; случайная погрешность; систематическая погрешность; электромеханическая катапульта; преобразование энергии; температурный градиент; вакуумная камера